Substrate Peptidomimetic Inhibitors of P. falciparum Plasmepsin X with Potent Antimalarial Activity. (18th August 2022) - Richardson, Lachlan W.; Ashton, Trent D.; Dans, Madeline G.; Nguyen, Nghi; Favuzza, Paola; Triglia, Tony; Hodder, Anthony N.; Ngo, Anna; Jarman, Kate E.; Cowman, Alan F.; Sleebs, Brad E.
Abstract: Plasmepsin X (PMX) is an aspartyl protease that processes proteins essential for Plasmodium parasites to invade and egress from host erythrocytes during the symptomatic asexual stage of malaria. PMX substrates possess a conserved cleavage region denoted by the consensus motif, SF h E ( h =hydrophobic amino acid). Peptidomimetics reflecting the P3 ‐P1 positions of the consensus motif were designed and showed potent and selective inhibition of PMX. It was established that PMX prefers Phe in the P1 position, di‐substitution at the β‐carbon of the P2 moiety and a hydrophobic P3 group which was supported by modelling of the peptidomimetics in complex with PMX. The peptidomimetics were shown to arrest asexual P. falciparum parasites at the schizont stage by impairing PMX substrate processing. Overall, the peptidomimetics described will assist in further understanding PMX substrate specificity and have the potential to act as a template for future antimalarial design. Abstract : Substrate mimicry : Substrate peptidomimetics were designed and showed potent inhibition of plasmepsin X (PMX). The peptidomimetics block PMX ligand processing, arrest asexual parasites at the schizont stage and potently kill P. falciparum parasites. The peptidomimetics will further assist in the understanding of PMX selectivity and in the development of PMX targeted antimalarials.